1998
DOI: 10.1136/bjsm.32.4.319
|View full text |Cite
|
Sign up to set email alerts
|

The New Zealand Rugby Injury and Performance Project: V. Epidemiology of a season of rugby injury.

Abstract: Objective-To describe the incidence, nature, and circumstances of injury experienced by a cohort of rugby union players during a full competitive club season. Methods-A prospective cohort study followed up 356 male and female rugby players throughout the 1993 competitive club season. Players were interviewed by telephone each week to obtain information on the amount of rugby played and the injury experienced. Results-Detailed information was collected for 4403 player-games and 8653 player-practices. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
3
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(188 citation statements)
references
References 10 publications
14
160
3
11
Order By: Relevance
“…Injuries also occur as the result of foul play, which is rarely penalized by the referee, with proportions ranging around 13% [14]. Of all injuries, 5% are as the result of foul play [6,8].…”
Section: Cause Of Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries also occur as the result of foul play, which is rarely penalized by the referee, with proportions ranging around 13% [14]. Of all injuries, 5% are as the result of foul play [6,8].…”
Section: Cause Of Injuriesmentioning
confidence: 99%
“…Most injuries occurring during a match affect the lower limbs (30% to 55% of injuries), followed by head and upper spinal injuries (14% to 30%), the upper limbs (15% to 20%) and finally the torso (10% to 14%) [7,[12][13][14][15]. It should be specified that in professional players, the head (including concussions) is the part of the body that is most often affected (25%), followed by the knee (14%-20%), thighs (13%-19%) and ankle (11%), then the shoulder (6.5%), hand (5.6%), leg (5.6%) and foot (3.5%) [8,[16][17][18][19].…”
Section: Location Of Injuriesmentioning
confidence: 99%
“…Coinciding with the decrease in scrum-related injuries, an increase in the incidence rate of catastrophic injuries resulting from open play was reported [57]. [30] and Garraway et al [5] reported that the tackle phase of play accounted for the majority of injuries, i.e. 40 and 48% respectively, while Roberts et al [31] reported 80% of all injuries occurred due to contact events.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…One possible explanation for the low rate of moderate and severe injuries is that injuries occurring late in the season may not be followed up as rigorously by the player and/or team medical or coaching staff in an amateur setting [42]. While followup physiotherapy assessments were arranged in one study, this was just for accuracy of injury recognition and diagnosis, with no long-term follow-up regarding injury severity recorded [30]. One barrier to injury surveillance within an amateur set-up is the availability of qualified medical professionals to assess, diagnose and rehabilitate injury, and this is evident in the discrepancies in follow-up periods following injury and lack of injury severity data [42,43].…”
Section: Injury Severitymentioning
confidence: 99%
See 1 more Smart Citation